Die Kommentierung des Buches Genesis. - Markschies, Christoph (Origenes Werke, 2010)
Origens work is mainly preserved only in fragments, as he was condemned as a heretic after his death. Thus only a fraction of his commentary on Genesis is still in existence, albeit a relatively large portion of the work and one of particular significance, as the story of the Creation is used to treat major themes in cosmology and views of destiny. Fragments of the history of the Patriarchs provide examples of Origens idiosyncratic hermeneutics in its allegorical and psychological interpretation.